Expression and molecular regulation of non-coding RNAs in HPV-positive head and neck squamous cell carcinoma - Guo, Dandan; Yang, Mei; Li, Shiyun; Zhu, Weiwei; Chen, Meixin; Pan, Jiayu; Long, Dan; Liu, Zhaohui; Zhang, Chunlin (Frontiers in Oncology, 2023)
Head and neck squamous cell carcinoma (HNSCC) is the sixth most prevalent malignancy worldwide. Accumulating evidence suggested that persistent HPV infection was closely related with a subset of HNSCC types, the incidence of HPV-positive HNSCC was increasing by years in recent decades. Though the carcinogenesis of HPV-positive HNSCC was not completely elucidated, it was well confirmed that E6 and E7, the main viral oncoproteins were responsible for the maintenance malignant transformation, promoting cell proliferation, and increasing tumor invasion. Moreover, compared with HPV-negative HNSCC, HPV-positive HNSCC showed some special clinical-pathological features, which was possibly related with the infection of HPV and their specific regulatory mechanism. Non-coding RNA (ncRNA) is a class of RNA lacking of protein-coding function, playing a critical regulatory role via multiple complex molecular mechanisms. NcRNA was an important regulation pattern of epigenetic modification, which can exert significant effects in HPV induced tumorigenesis and progression through deregulating downstream genes. However, the knowledge of ncRNAs was still limited, a better understanding of ncRNAs could provide some insights for exploring carcinogenesis mechanism and identifying valuable biomarkers in HPV-positive HNSCC. Therefore, in this review, we mainly focus on the expression profile of ncRNAs (including lncRNA, miRNA, circRNA) and explore the regulatory role in HPV-positive HNSCC, aiming to clarify the regulatory mechanism of ncRNAs and screen valuable biomarkers for HPV-positive HNSCC.